Readiness, attitude and motivation of Penggerak Masyarakat Orang Asli (PMOA) in the preaching activity to indigenous peoples in Malaysia - Abdul Ghafar Don,; Anuar Puteh,; Razaleigh Muhamat @ Kawangit,; Zulkefli Aini,; Badlihisham Mohd Nasir,; Marlon Guleng, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The main purpose of the Islamic Proclamation is to persuade people to believe in Islam and to accept Islam as their way of life. This article is the result of a study on the level of readiness, attitude, motivation, facilities, infrastructure and challenges of the Indigenous Peoples Movement or Penggerak Masyarakat Orang Asli (PMOA) in assessing the level acceptance towards Islam. A survey was conducted and distributed to 120 respondents. The data were analyzed using Statistical Package for the Social Sciences (SPSS) for Windows version 22. The results of this study showed that PMOA had adequate preparation in the context of the implementation of the preaching of indigenous people with high mean values of 3.98. Meanwhile, the PMOA motivation level was very high with a mean score of 4.24. With regard to the comfort and convenience of the Orang Asli villages, respondents’ views also high with an overall mean value of 3.46. In terms of challenges, the PMOA showed a moderate level of mean, 3.32 while the approach aspect was high mean values of, 4.24. The overall findings of the study showed that the PMOA possessed all the required aspects. However, all of the elements that was measured must be enhanced from time to time.